Analisa Pemberian Azitromicin Sebagai Obat COVID-19 pada Pasien Terkonformasi Positif di Indonesia - Haryanto, Kusno; Marlinda Sari, Liska (Publikasi Indonesia, 2022)
Antibiotics are given to corona patients if the doctor feels it is necessary because the patient is infected by certain bacteria. For example, a coronavirus patient is exposed to bacterial pneumonia. One type of antibiotic on the market is Azithromycin. Azithromycin is currently widely available in pharmacies such as in the Jakarta area. It is possible to increase the sales turnover of pharmacists only to the extent of selling the drug without educating consumers. The initial step to overcome the rampant sales of Azithromycin which is allegedly being sold freely among the public is to conduct a survey on the distribution of Azithromycin in pharmacies in DKI Jakarta, which is one of the barometer areas in handling COVID-19 in Indonesia. The aims of this study were: 1) to determine the availability of Azithromycin in pharmacies in the DKI Jakarta area; 2) to find out how much the public's demand for Azithromycin is in pharmacies in the DKI Jakarta area; 3) to know the public's understanding of the use and impact of using Azithromycin; 4) knowing whether or not there is education given by pharmacists to the community regarding the use and impact of using Azithromycin. The sample studied was 200 respondents in the Jakarta area who stated that they had bought Azithromycin in handling COVID-19. Data analysis used multiple linear regression. The results of the study concluded: 1) Public understanding of antibiotics and information on drug administration by pharmacists have a negative relationship towards the spread of Azithromycin, which means that if public understanding of antibiotics and information on drug administration by pharmacists has a low value, it will encourage an increase in distribution. Azithromycin in the community; 2) The correlation between public understanding of antibiotics and information on drug administration by pharmacists with the distribution of Azithromycin has a fairly strong category; 3) Public understanding of antibiotics and information on drug administration by pharmacists have a very significant influence on the distribution of Azithromycin.